2020
DOI: 10.1080/23802359.2020.1800431
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Wiesnerella denudata (Mitt.) Steph. (Wiesnerellaceae, Marchantiophyta)

Abstract: We completed chloroplast genome of Wiesnerella denudata (Mitt.) Steph, only one species of the monotypic Wiesnerella genus and family Wiesnerellaceae Inoue. It is 122,500 bp and has four subregions: 82,143 bp of large single copy (LSC) and 20,009 bp of small single copy (SSC) regions are separated by 10,174 bp of inverted repeat (IR) regions including 132 genes (88 protein-coding genes, eight rRNAs, and 36 tRNAs). The overall GC content is 28.8% and those in the LSC, SSC, and IR regions are 26.4, 24.6, and 42.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
1
1
Order By: Relevance
“…Phylogenetic trees present that our W. denudata mitochondrial genome is clustered with the previous W. denudata mitogenome with high supportive values ( Figure 1(A) ), which is different from the previous study based on chloroplast genome (Choi et al. 2020 ). It also displays that Wiesnerellaceae is clustered with Monosoleniaceae, not Ricciaceae ( Figure 1(A) ), which is incongruent to the previous study (Crandall-Stotler et al.…”
contrasting
confidence: 99%
“…Phylogenetic trees present that our W. denudata mitochondrial genome is clustered with the previous W. denudata mitogenome with high supportive values ( Figure 1(A) ), which is different from the previous study based on chloroplast genome (Choi et al. 2020 ). It also displays that Wiesnerellaceae is clustered with Monosoleniaceae, not Ricciaceae ( Figure 1(A) ), which is incongruent to the previous study (Crandall-Stotler et al.…”
contrasting
confidence: 99%
“…This result suggests that next-generation sequencing technology that provides a large number of short reads can be used to provide evidence for the existence of endosymbiont species using DNA extracted from insect species. These results draw comparison to previous studies that have successfully identified a multiple number of complete organelle or bacterial genomes from one NGS library [12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionsupporting
confidence: 65%
“…This suggests that these insect-hosted fungal endosymbionts have been evolved independently from the other fungal species in the Ophiocordycipitaceae family. Owing to the advantages of NGS raw reads, which can detect sequences from unknown or unexpected organisms [12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], we successfully identified the complete mitogenomes of WBPH fungal endosymbionts within the NGS raw reads, suggesting that we can understand their phylogenetic positions of fungal symbiont with high resolution without the need to isolate the symbiont from the host. Furthermore, our study shows that NGS raw reads of insects generated in the future can be used to pinpoint further fungal endosymbionts that have previously been difficult to identify.…”
Section: Discussionmentioning
confidence: 99%